Environmental & architectural phenomenology. Vol. 24, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2013)
Vol. 24, No. 2, Spring 2013 (includes “items of interest,” and works related, and tributes, to Henri Bortoft).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals